Optimization of Islamic Religious Education and Ethics Learning With The Integration of Contextual Teaching and Learning With Digital Technology - Sukmawati, Sita; Inayati, Nurul Latifatul (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study examines the optimization of Islamic Education (PAI) and Character Education learning through the integration of Contextual Teaching and Learning (CTL) with digital technology at SMK Negeri 7 Surakarta. The CTL method is used to connect instructional materials with students' real-life experiences, while digital technology is leveraged to enhance their engagement and comprehension. Using a descriptive qualitative approach, this research collected data through observations, interviews, and document analysis. The findings suggest that integrating CTL and digital technology enhances student participation, deepens their understanding of religious concepts, and promotes critical and reflective thinking. However, challenges remain, such as low learning motivation, suboptimal Quranic reading skills, and a lack of internalization of religious values. To address these issues, teachers implement strategies such as habitual worship practices, project-based learning, and the use of interactive digital media. These findings affirm that integrating CTL and digital technology can create a more relevant, engaging, and meaningful PAI learning experience for vocational school students.